The women's movement and women's employment in nineteenth century Britain - Jordan, Ellen, 1938- (London ; New York : Routledge, 1999)
Ellen Jordan's treatment of the expansion of middle-class women's work is perhaps the most comprehensive available and is a valuable complement to existing works on the social and economic history of women.
Part PART I Introduction -- chapter 1 The question of middle-class women's work -- part Part II THECONSTRAINTSONWOMEN ' SWORK -- chapter 2 The constraints of gentility: the separation of work and home and the breadwinner norm -- The seperation of work and home and the emergence of the male breadwinner norm -- chapter 3 The constraints of femininity -- The domestic ideology -- chapter 4 What was 'women's work'? -- The patriarchal household and employers' 'knowledge' -- chapter PartIIISTRONG -M INDEDWOMEN -- chapter 5 Bluestockings, philanthropists and the religious heterodoxy -- chapter 6 Determining girls' education -- Governesses and the ladies' colleges -- chapter 7 Transforming nursing: female philanthropy and the middle-class nurse -- Female philanthropy and the middle class nurse -- part PART I V The Women's Movement -- chapter 8 Redefining 'women's sphere' -- Confronting the domestic ideology -- chapter 9 Redefining 'women's work' -- Creating a 'pull factor' -- chapter 10 Redefining 'ladies' work' -- Creating a 'push factor'.
Includes bibliographical references (pages 230-247) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Women -- Employment -- Great Britain -- History -- 19th century; Feminism -- Great Britain -- History -- 19th century; Women -- Great Britain -- Social conditions; Femmes -- Travail -- Grande-Bretagne -- Histoire -- 19e siècle.; Féminisme -- Grande-Bretagne -- Histoire -- 19e siècle.; Femmes -- Grande-Bretagne -- Conditions sociales; BUSINESS & ECONOMICS -- Labor; POLITICAL SCIENCE -- Labor & Industrial Relations; Feminism; Women -- Employment; Women -- Social conditions; Great Britain; Berufstätigkeit; Frau; Frauenbewegung; Großbritannien; Vrouwenarbeid; Vrouwenbeweging; Verenigd Koninkrijk van Groot-Brittannië en Noord-Ierland.; Geschichte 1840-1900.; 1800-1899; History